Histologi Jaringan Hepar Mencit (Mus Musculus) yang Difiksasi dengan Larutan Carnoy dengan Variasi Waktu 4 Jam, 8 Jam dan 12 Jam - Afrida, Arin Dwi; Priyatno, Djoko (Poltekkes Kemenkes Semarang, 2021)
Histopathological examination is a routine examination process for each tissue in the anatomic pathology laboratory. The stages in making histology preparations are fixation stages. The type of solution that can be used as a fixative solution other than 10% NBF is Carnoy's solution. Carnoy's solution is a fixative solution with a relatively fast fixation process of about 1-4 hours. The advantages of Carnoy's solution can lyse erythrocytes and dissolve lipids, have the ability to maintain cell nuclei, and retain glycogen. The purpose of this study was to determine the histology of the liver tissue preparations of mice (Mus Musculus) which were fixed using Carnoy's solution with time variations of 4 hours, 8 hours, and 12 hours. This is an observational research with descriptive research design criteria. The results of the histology of the liver tissue preparations of mice (Mus Musculus) which were fixed using the 10% NBF solution group obtained 100% good preparations. In the Carnoy solution group with a time of 4 hours, it gave 2.2% results of poor preparations and 97.78% of good preparations. While the treatment group with Carnoy's solution with a time of 8 hours obtained as many as 11.11% of preparations that were not good and 88.89% of good preparations. and in the Carnoy solution group with a time of 12 hours, there were 44.44% of the poor preparations and 55.56% of the good preparations.